The transient impact of the African monsoon on Plio-Pleistocene Mediterranean sediments - B. de Boer; M. Peters; L. J. Lourens (Climate of the Past, 2021)
Over the Plio-Pleistocene interval a strong linkage exists between northern African climate changes and the supply of dust over the surrounding oceans and continental runoff towards the Mediterranean Sea. Both these signatures in the sedimentary record are determined by orbital cycles influencing glacial variability on the one hand and northern African monsoon intensity on the other hand. In this paper, we use the intermediate-complexity model CLIMBER-2 to simulate African climate during the Plio-Pleistocene between 3.2 and 2.3 million years ago (Ma) and compare our simulations with existing and new climate reconstructions. The CLIMBER-2 model is externally forced with atmospheric CO 2 concentrations, ice sheet topography, and orbital variations, all of which strongly influence climate during the Pliocene and Pleistocene. Our simulations indicate that the records of northern Africa climate oscillate in phase with climatic precession. For the Earth's obliquity cycle, the time lag between the 41 000-year component in insolation forcing and the climatic response increased after inception of Northern Hemisphere (NH) glaciation around 2.8 Ma. To test the outcome of our simulations, we have put emphasis on the comparison between the simulated runoff of grid boxes encompassing the Sahara desert and the Sahel region and the sedimentary records of marine sediment cores from ODP Site 659 (Atlantic Ocean) and ODP Site 967 (Mediterranean). In this study we will show for the first time an extended Ti∕Al record of Site 967 down to 3.2 Ma. This record strongly correlates with runoff in the Sahara and Sahel regions, whereas correlation with the dust record of Site 659 is moderate and slightly improves after NH ice sheet inception. We investigated the transient variability of the individual and combined contributions of the Sahel and Sahara regions and found significant transient behaviour overlapping the inception of NH ice sheets (2.8 Ma) and the Plio-Pleistocene transition (2.6 Ma). Prior to 2.8 Ma, a larger contribution from ...